2015
DOI: 10.1016/j.tcm.2015.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Ionic mechanisms of arrhythmogenesis

Abstract: The understanding of ionic mechanisms underlying cardiac rhythm disturbances (arrhythmias) is an issue of significance in the medical science community. Several advances in molecular, cellular and optical techniques in the past few decades have substantially increased our knowledge of ionic mechanisms that are thought to underlie the arrhythmias. The application of these techniques in the study of ion channel biophysics and regulatory properties has provided a wealth of information, with some important therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 61 publications
(122 reference statements)
2
14
0
Order By: Relevance
“…Several studies have suggested myocardial ischemia as a variant of progressive prolongation of QT interval and the corresponding action potential duration, which may cause fatal arrhythmias, such as TdP and sudden cardiac death (9)(10)(11). According to these studies, TdP episodes, which are triggered by ischemia or other conditions, may either terminate spontaneously producing some misleading symptoms, similar to the present case (with transient seizure episodes at admission), or may lead to more lethal arrhythmias.…”
Section: Discussionsupporting
confidence: 67%
“…Several studies have suggested myocardial ischemia as a variant of progressive prolongation of QT interval and the corresponding action potential duration, which may cause fatal arrhythmias, such as TdP and sudden cardiac death (9)(10)(11). According to these studies, TdP episodes, which are triggered by ischemia or other conditions, may either terminate spontaneously producing some misleading symptoms, similar to the present case (with transient seizure episodes at admission), or may lead to more lethal arrhythmias.…”
Section: Discussionsupporting
confidence: 67%
“…The current flow in the ventricular tissue was driven by active ion exchange across the cell membrane. Many researchers have made a great contribution in developing mathematical models of these ionic properties in the cardiac myocyte [914]. In this study, we adopted the ionic myocyte model from Ten Tusscher et al [12].…”
Section: Methodsmentioning
confidence: 99%
“…We will focus on the roles of intracellular Ca + dynamics, gap junctions, myofibroblasts, and cell‐structural and histoanatomic features of the myocardium in the genesis of cardiac arrhythmias. The updated, general principles of electro‐centric arrhythmogenesis can be assessed by reference to another review article …”
Section: Introductionmentioning
confidence: 99%
“…The updated, general principles of electro-centric arrhythmogenesis can be assessed by reference to another review article. 13…”
Section: Introductionmentioning
confidence: 99%